FORMULATION AND EVALUATION OF SELF-NANOEMULSIFYING DUAL DRUG DELIVERY SYSTEM OF CELECOXIB AND CURCUMIN. - Shubham Singh; Dr. Jai Narayan Mishra (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The goal of this research is to create new lipid-based SNEDDS (self-nanoemulsifying drug delivery systems) Celecoxib & Curcumin. A Sonication method was used to determine the solubility in equilibrium of celecoxib and curcumin in various oils and other components Surfactants (Tween-20, Tween-80, Span-20, Span-80) and cosurfactants (Polyethylene glycol-400, Isopropyl alcohol, Glycerol) and water. Solubility, partition coefficient and compatibility tests were evaluated. The formulation was evaluated for optical clarity, phase separation study, Analysis of globular size, self-emulsification time, and zeta potential electrophoretic mobility & transmission electron microscopy (TEM). Form invitro dissolution study % cumulative release of celecoxib and curcumin is more when comparing SGF to SIF (simulated gastric fluid to simulated intestinal fluid).